Analysis of heat transfer characteristics of a coaxial air jet on a hot surface: An experimental study with circular nozzles of different arrangements - Chetan Kumar; Vasudeva Madav (Results in Engineering)
Coaxial jets are widely utilized in various engineering applications where highly localized heat transfer is the requirement, including combustion systems, cooling technologies, propulsion systems, material processing, and environmental control. This study investigates the effects of air jet impinging on a hot surface by varying the nozzle-to-plate distance-to-diameter ratio (Z/d) at values of 2, 4, 6, and 8, along with adjustments in the inner-to-outer jet exit distance ratio (H/d), set at -1, 0, and +1, under different Reynolds numbers (Re) of 5000, 10000, 15000, and 20000. The study provides a comparative analysis of Nusselt number achieved by coaxial jet configurations against conventional circular single-jet impingement, highlighting significant improvements in heat transfer rate The findings demonstrate that coaxial jets markedly enhance heat transfer, particularly at the stagnation point of the foil surface, with the H/d = +1 configuration yielding the best result. An improvement of 191 % is observed for Z/d = 6 and H/d = +1 case when Re is increased from 5000 to 20000, Proving the impact of increase in Re on stagnation Nusselt Number. When stagnation Nusselt number is compared for normal circular jet with that of H/d = +1 case in coaxial jet, a maximum of 88.73 % improvement is seen. This study is important because the results offer valuable insights for optimizing air jet impingement techniques to improve thermal management across a range of industrial applications ranging from Gas turbines to manufacturing industries where localized cooling is the major requirement. The correlations to calculate the stagnation Nusselt number for three configurations of the coaxial jet are developed.